Penyatuan Kalender Islam: Mendialogkan Wujûd al-Hilâl dan Visibilitas Hilal - Susiknan Azhari (Universitas Islam Negeri Jakarta, 2013)
Abstract: Unification of the Islamic Calendar: A Dialogue on Wujûd al-Hilâl and the Visibility of Hilâl. Within the vocabulary of the Islamic calendar, particularly in Indonesia, the terms al-Hilâl and the sighting or “visibility” of the hilal (imkân al-ru’yah) are recognised. Wujûd al-hilâl is a creative synthesis or half way between ijtimâ’ (qabl al-ghurûb) and the theory of the visibility of the hilâl or, in other words, half way between pure hisab (calculating the hilâl) and ru’yah (the sighting of hilâl). Therefore, for the theory of wujûd al-hilâl, the method used in starting the first day and a new month on the Islamic calendar is not merely the process of the occurrence of astronomical conjunctions but also considering the position of hilâl at sunset. Meanwhile, the visibility of hilâl is a construction of theories that which are sourced from the experience of observers. As a result, various typologies are created. In order to unite both concepts, an assertive and continuous dialogue is required.Keywords: hilâl, hisâb, ru’yah, matla‘Abstrak: Penyatuan Kalender Islam: Mendialogkan Wujûd al-Hilâl dan Visibilitas Hilal. Dalam khazanah pemikiran kalender Islam, khususnya di Indonesia, dikenal istilah wujûd al-hilâl dan visibilitas hilal (imkân al-ru’yah). Kehadiran wujûd al-hilâl merupakan sintesis kreatif atau jalan tengah antara teori ijtimâ‘ (qabl al-ghurûb) dan teori visibilitas hilal atau jalan tengah antara hisab murni dan rukyat murni. Oleh karena itu, bagi teori wujûd al-hilâl metode yang digunakan dalam memulai tanggal satu bulan baru pada kalender Islam tidak semata-mata proses terjadinya konjungsi tetapi juga mempertimbangkan posisi hilal saat matahari terbenam. Sementara itu visibilitas hilal adalah bangunan teori yang bersumber dari pengalaman para pengamat. Sehingga melahirkan bermacam-macam tipologi. Untuk memadukan keduanya diperlukan dialog yang asertif dan berkelanjutan.Kata Kunci: hilal, hisab, rukyat, matlakDOI: 10.15408/ajis.v13i2.931